Կերպարանափոխությունը առածային խոսույթում. մարդկային էության բնութագրի լեզվաճանաչողությունը - Շալունց, Նարե (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Within proverbial discourse, the linguocognitive model of metamorphosis reveals how French and Armenian proverbs portray human nature and the cognition of human traits. In this context, human nature and behavioral patterns are analyzed through the prism of animal imagery and conceptual metaphors, and the negative connotations associated with metamorphosis are highlighted. At the core of this analysis lies the issue of behavioral and, more broadly, identity shifts, analyzed both on an ontological plane and at the level of conceptual perception, at the intersection of being and seeming. Furthermore, the analysis emphasizes the role of causality in the construction of a new identity. It should be noted that proverbial discourse highlights the immutability of human nature: the external manifestations of metamorphosis do not result in any substantive internal change. From a linguocognitive and linguostylistic perspective, the proverbs under study reveal cognitive models that illustrate the failure of external influence to alter innate attributes, as well as the mapping of human nature onto behavioral patterns.
Keywords: Բանասիրություն